Um olhar crítico sobre o Conselho Nacional de Turismo: articulação do setor, legitimidade e auto-interesse na construção das políticas públicas - Cavalcanti, Paloma Albino Borba (2006)
This work examines the tourism policy process in Brazil and its institutional realm of participative stances in federal level. For that end, it observes the Brazilian National Tourism Board – BNTB and its functioning during the 2003-2006 period with the purpose of identifying and analyzing its political dynamics considering its attributions and representativity. Taking as a starting point some theoretical studies from Political Science and Public Administration, this research bases its analytical procedures on two perspectives: on one side, on the constitution of participative stances in the exercise of democracy, namely, on the increase of public policy councils as deliberative stances and, on the other, on the interaction dynamics V between different actors and interest groups in the production of public policies in general, mainly, considering the specifics of tourism public policies. This way, this research aims to build an analysis on the contradictions and limitations of the BNTB that is, simultaneously, a participative stance in the context of deliberative democracy and as a governance mechanism towards the tourism policy process.